Does ambient temperature affect on exercise-induced fatigue and sustainability of repetitions in cadet wrestlers? - Mirzaei, B.; Lotfi, N.; Bolboli, L. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The purpose of the present study was to investigate the effect of ambient temperature on exercise-induced fatigue and sustainability of repetitions in cadet wrestlers. METHODS: 21 cadet wrestlers (age: 15.04±0.8 years, weight: 59.20±12.67 kg, height: 163.47±7.39 cm, body fat: 10.03±3.39%) participated as subjects in this study. Based on body composition and anthropometric profiles, subjects were divided into three similar groups. After providing the desired temperature (30, 18 and 10 °C), subjects were asked to complete a Wrestling Technique Based Circuit Training protocol. Fatigue level was measured by Likert scale (5-point scale) before, immediately and 30 minutes after exercise and the ability of sustainability of repetitions was measured by counting number of implemented techniques. Independent Samples t-test, ANOVA repeated measures, one-way ANOVA and Bonferroni post-hoc tests were used to analyze the results at a significance level of p< 0.05.RESULTS: The results showed that the levels of fatigue increased significantly after exercise in all groups and it was observed significant difference between high-temperature (HT) and low-temperature (LT) groups with normal-temperature (NT) group. In addition, the ability to sustainability of repetitions decreased significantly in all groups in second-round and this reduction was higher in HT and LT groups compared to NT group. Also, significant differences were observed between HT- NT groups and LT - NT groups. However, after 30-minutes of active rest despite the decrease in fatigue levels, significant difference was observed between the levels of pre- exercise and after 30-minute recovery time in all groups. CONCLUSION: The results showed that heat stress can aggravate exercise-induced fatigue in cadet wrestlers. Thus, it is suggested that special attention should be paid to ambient temperature of competition and training gyms of this age group.